The twentieth-century performance reader - Huxley, Michael; Witts, Noel (Abingdon, Oxon Routledge, 2002)
The Twentieth Century Performance Reader is the key introductory text to all types of performance. Extracts from fifty practitioners, critics and theorists from the fields of dance, drama, music, theatre and live art make up an essential sourcebook for students, researchers and practitioners.A bestseller since its publication in 1996, this second edition has been fully updated and includes:* New writings by practitioners and theorists* Notes about each writer* A completely new introduction.Each extract is fully supplemented by a contextual summary, a biography of the writer, and suggestions for further reading. Organised alphabetically, this reader makes it possible to compare major writings on all types of performance in one volume. The ways in which different performance practitioners' ideas inter-relate are pointed out in a series of detailed cross-references for readers. In so doing it becomes clear that one of the key features of twenty first century performance is its boundlessness and its capacity to cross borders.All who enjoy or work with live innovative performance will find this book invaluable.